Innovative Housing Policy and (Vulnerable) Residents’ Quality of Life - Frątczak-Müller, Joanna (Frontiers in Psychology, 2022)
The subject of the current study is the process of implementing the social housing policy and its impact on increasing the quality of life of vulnerable people. The analysis is related to the Social Housing Program introduced by the city of Gdańsk (Poland). The study has been carried out using the case study method with the use of document analysis, analysis of existing data, and five in-depth interviews with program managers. The theoretical framework has been developed around three major explicatory perspectives: multi-level governance, quality of life, and social exclusion. Meeting the housing needs is one of the primary tasks of local governments. If such a policy is to be called positive, it should be combined with social policy tasks related to social inclusion and it should be carried out through partnerships forming housing cooperation networks. A characteristic feature of the cooperation is the cross-sectoral nature of the actors. The results have revealed a significant positive relationship between the use of social housing tools and the quality of satisfying the living needs of the residents. This study contributes to the discussion by revealing the role of social work and social and professional activation in meeting housing needs. The results suggest that a combination of housing and social policy measures can help vulnerable people develop social competencies conducive to housing maintenance and increase the social cohesion of local environments.